Novel protocol for selection of SARS-CoV-2 convalescent plasma donors - Ostojić, Gordana; Šupić, Gordana; Karličić, Vukoica; Karličić, Marija; Ristanović, Elizabeta; Kovačević, Milan; Abazović, Dzihan; Gojkov , Dragana; Stanojević, Ivan; Vukosavljević, Miroslav; Vojvodić, Danilo (Vojnosanitetski pregled, 2022)
Background/Aim. Severe Acute Respiratory Syndrome Corona Virus 2 (SARS-CoV-2) 2019 infection represents a global problem. At this moment, in October 2020, there is no vaccine or efficient treatment for infected patients. Treatment with blood plasma rich with anti-SARS-CoV-2 specific antibodies might be a safe, and effective therapy for COVID-19 patients. Methods. A total of 768 patients were analyzed in this study, whose samples were collected in a time interval from May 1, 2020, till August 15, 2020. Patients were enrolled in the study from COVID-19 hospitals and out-clinics. In-house ELISA tests were developed to measure the concentration of anti-S1S2 spike and anti-nucleoprotein (np) (IgG, IgA, IgM) SARS-CoV-2 antibodies. Blood convalescent plasma was selectively collected from recovered patients according to specific antibodies concentration. Results. The highest concentrations of anti-S1S2 spike or anti-np specific IgG antibodies were detected in patients with the moderate/heavy clinical form of the infection. An extremely high concentration of anti-S1S2 spike IgG and anti-np IgG was demonstrated in 3% and 6% of patients who recovered from severe COVID-19, respectively. Of tested hospitalized patients, 63% and 51% had modest levels of anti-S1S2 spike and anti-np, respectively. After 60 days, in our selected donors, concentrations of anti-S1S2 spike IgG and anti-np IgG antibodies increased in 67% and 58% of donors, respectively. Conclusion. In-house developed ELISA tests enable a novel protocol for selecting convalescent blood plasma donors recovered from SARS-CoV-2 infection.
Keywords: antibody specificity; clinical protocols; covid-19 serotherapy; enzyme-linked immunosorbent assay; SARS-CoV-2; plasma; tissue donors